Propriedades anti-inflamatórias e potencial para fitoterapia da espécie vegetal, de uso tradicional da região amazônica, Bellucia dichotoma - (:unkn) unknown (Universidade Federal do Amazonas, 2022)
To the Bothrops atrox snake is attributed the majority of ophidic accidents in the northern region of Brazil and its envenomation is characterized by intense local lesions, hemostatic disorders, and relevant inflammation. In some regions of the country where the treatment of snake accident victims is precarious, medicinal plants have been presented as an alternative treatment or as an adjunct to serotherapy. This work aimed to evaluate the anti-inflammatory potential of Bellucia dichotoma, a plant species native to the Amazon region, which is used in traditional medicine to treat snake poisoning, for the development of a phytotherapeutic with antiophidic properties. The dried extract of B. dichotoma was evaluated for the following in vitro activities: cytotoxicity and blockade in the inflammatory activity induced by B. atrox venom in differentiated macrophages of immortalized leukemic cell line - THP-1- by quantification of cytokines, reactive species (ROS) production and COX expression, and evaluation of the healing potential by cell motility assay in human fibroblast cells of the MRC-5 line. An oral acute toxicity test of B. dichotoma extract was performed on Wistar rats to evaluate the pharmacological safety of the species and its use in herbal formulations. An effervescent granule-type solid oral pharmaceutical form was developed, evaluated for thermal stability and physicochemical characterization, and tested for its anti-inflammatory potential in paw edema induced by B. atrox venom. The results showed that cell viability in THP-1 cells from the dry extract of B. dichotoma was approximately 100% up to the concentration 50μg/ mL, but the concentration capable of causing death of the same proportion of cells is above 1000μg/ mL. In the cytotoxic analysis of B. atrox venom the dose 1000μg/ mL able to cause 100% cell death and the IC50 of 527.8 μg/mL determined by log curve. Based on these results, we performed the activity assays for blocking the inflammatory response induced by B. atrox venom at a dose of 527.8 μg/mL in THP-1 macrophages. The results showed that macrophages challenged with B. atrox venom had increased production of the pro-inflammatory cytokine TNF- of the cytokine IL-12p70, and that when treated with B. dichotoma extract they showed decreased production of these cytokines. B. dichotoma extract showed a dose-dependent antioxidant effect by reducing oxidative stress induced by B. atrox venom in THP-1 macrophages. B. atrox venom did not induce COX production in the THP-1 cell line used, so it is not possible to evaluate the potential of B. dichotoma for blocking the lipid mediator production pathway. When the healing potential of B. dichotoma was evaluated, in the assay with MRC-5, the cells treated with the plant extract at doses 1 and 5 μg/mL showed cell migration up to 20% more effective than the positive control Vitamin C, used as gold standard. In thermal characterization, thermal stability of the dried extract was observed, showing only two mass loss events, in the intervals 25-105ºC (Δm=4.68%) and 239- 318ºC (Δm=19.06%). From the acute toxicity test no signs of toxicity of B. dichotoma extract were observed up to a dose of 2000 mg/Kg, which corresponds to twice the dose recommended by ANVISA to evaluate toxicity of substances. From the previous results, an effervescent granulate based on the B. dichotoma extract was developed. With regard to granulates, the formulation that presented the best organoleptic and effervescence characteristics was used to evaluate the blocking effect of the edematogenic action of Bellucia dichotoma. The bench batch with a final weight of 4 grams and 7.25% dry extract of B. dichotoma obtained using the malax molting process showed good effervescence, without lump formation, when effervesced in 60 mL of distilled water. The results of the antiedematogenic assay showed that the pellet at a concentration of 566.6 mg/kg was as effective as the positive control, the antibotropic serum (ABS), in reversing the edema induced by B. atrox venom in mouse paws. Thus, the capacity of Bellucia dichotoma to block inflammatory effects induced by Bothrops atrox snake venom and the phytotherapeutic potential of this plant species were evidenced. These findings are of great relevance to the local population of the Amazon region, who use Bellucia dichotoma as an alternative or 9 complementary therapeutic resource to the serum that, although it is the standard treatment, has limitations regarding administration and in reversing severe local effects induced by the venom.
Keywords: Venenos de Crotalídeos; Cobras venenosas - Veneno; Fitoterapia; Antivenenos; Plantas medicinais; CIENCIAS BIOLOGICAS: IMUNOLOGIA; Acidentes ofídicos; Plantas medicinais; Bellucia dichotoma; Fitoterapia; Snakebites; Medicinal plants; Bellucia dichotoma; Phytotherapy